Enumeration and Identification of Fungi from Selected Local Spices Sold in Minna Nigeria - Oluwafemi Adebayo, Oyewole; Susan Kingsley, Okeke; Saheed Abdulameen, Adedeji; Hasiya, Mustapha; Japhet Gaius, Yakubu (Covenant Journal of Physical and Life Sciences, 2021)
Spices are defined as any plant substance either in powdered form, broken or as a whole which have aromatic features capable of influencing a change of taste or smell of food and beverages. This study was aimed at enumeration and identification of fungi from selected food spices from Minna Nigeria markets. Samples of ginger, chilli pepper, turmeric, nutmeg, locust beans, black pepper, clove and garlic were collected randomly from two different markets; Kure and Bosso in Minna metropolis. The proximate analysis of the samples (moisture, total ash, crude fiber, fat, and carbohydrate) was determined. Standard microbiological techniques were used to enumerate, isolate and identify the fungi in the samples. The proximate composition showed that the highest moisture content was found in turmeric (15.85 %). The highest ash content was in cloves (9.70 %). The highest crude fibre was present in chilli pepper (10.69 %) and the highest carbohydrate was found in garlic (74.07 %). Locust beans had the highest oil extract (24.60 %) and crude protein (22.75 %). The highest fungal count was obtained in nutmeg (1.36Ã—104 cfu/g) followed by ginger (9.2x103 cfu/g). The lowest fungal count was obtained in turmeric and garlic (1x102 cfu/g). The fungi isolated and identified were as follows: Aspergillus niger, A. fumigatus, A. flavus, A. terrus, Saccharomyces cerevisiae and species of Aspergillus, Mucor, Penicillium, Trichophyton, and Chrysosporium. The results of this study showedÂ that the selected local spices harbour different fungal species. Therefore, proper handling hygiene and storage is recommended.